Exploring the Effect of Assisted Repeated Reading on Incidental Vocabulary Learning and Vocabulary Learning Self-Efficacy in an EFL Context - Soleimani, Habib; Mohammaddokht, Farnoosh; Fathi, Jalil (Frontiers in Psychology, 2022)
The purpose of the current study was to investigate the effect of two types of repeated reading (i.e. assisted and unassisted) on incidental vocabulary learning of Iranian English as a Foreign Language (EFL) learners. In so doing, a sample of 45 intermediate EFL students from two intact classes of a language institute were selected as the participants. The two classes were randomly assigned to an unassisted group (N=21) who were required to just read and an assisted group (N= 24) who were asked to read and listen to 24 short texts several times. The assisted group employed their smartphones to listen to the audio files of the short stories. The data were gathered via a researcher-made vocabulary test and vocabulary learning self-efficacy scale. The results of ANCOVA revealed that although both types of repeated reading contributed to enhancing vocabulary learning of the participants, assisted repeated reading led to significantly greater EFL vocabulary gains. Additionally, the findings revealed that both assisted and unassisted repeated reading improved vocabulary learning self-efficacy of the participants and there was not a significant difference between the two types of interventions. The findings of the present study have implications for EFL researchers and practitioners.